JNK inhibitor IX restrains pancreatic cancer through p53 and p21 - Shi, Jingwei; Yang, Xing; Kang, Qi; Lu, Jian; Denzinger, Maximilian; Kornmann, Marko; Traub, Benno (Frontiers in Oncology, 2022)
Abstract: Novel treatment options for pancreatic cancer are desperately needed. De-regulated kinases can be regularly detected in pancreatic cancer. Multiple pathway inhibitors were developed to exploit these features, among them selective inhibitors of the c-Jun N-terminal kinase isoforms 1 and 2 (JNK1 and 2). We evaluated the effectiveness of four different JNK inhibitors on pancreatic cancer cell lines. Cell mobility and migration were evaluated in scratch assay and Boyden chamber assay. Mechanism of cell death was analyzed via apoptosis assays in FACS and immunoblotting as well as cell cycle analysis via FACS, and qPCR. JNK2 knockout cells were generated using siRNA transfection. Among the inhibitors, JNK inhibitor IX (JNK-in-IX), designed as specific inhibitor against JNK2 was proven highly effective in inhibiting cell growth, mobility and migration. We were able to show that JNK-in-IX caused G2 arrest mediated through p53 and p21 while it was without effect on apoptosis. Interestingly, JNK-in-IX acted independently of its primary target JNK2. In summary, JNK-in-IX was shown highly effective in pancreatic cancer. This study underlines the need for modeling systems in testing therapeutic options as JNK2 was previously not indicated as potential target.